2008
DOI: 10.1016/j.fertnstert.2007.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst development rate impacts outcome in cryopreserved blastocyst transfer cycles

Abstract: Cryopreserved day-5 blastocysts have higher implantation rates and trend toward improved pregnancy outcomes compared with cryopreserved day-6 blastocysts. This suggests that embryo development rate may, in part, predict implantation and subsequent FBET outcomes, although embryos not achieving the blastocyst stage until day 6 still demonstrate acceptable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 20 publications
5
35
1
Order By: Relevance
“…Comparable pregnancy and live birth rates were achieved in both groups. These results stand in contrast to an earlier, similar study by Levens et al in 2008 showing a higher implantation rate in day 5 blastocysts than in day 6 blastocysts transferred on the 6th day of progesterone, although in this study, live birth rates were also similar between groups [9].…”
Section: Introductioncontrasting
confidence: 99%
“…Comparable pregnancy and live birth rates were achieved in both groups. These results stand in contrast to an earlier, similar study by Levens et al in 2008 showing a higher implantation rate in day 5 blastocysts than in day 6 blastocysts transferred on the 6th day of progesterone, although in this study, live birth rates were also similar between groups [9].…”
Section: Introductioncontrasting
confidence: 99%
“…Some people have reported that the anabiosis rate of D5 early blastocysts (87-91%) is higher than that of expanded blastocysts (55-71%), so early blastocysts are more suitable to vitrification (Vanderzwalmen et al 2002;Hiraoka et al 2004). Some people have believed that vitrified D5 expanded blastocysts have higher clinical pregnancy rates (Levens et al 2008). Furthermore, it is unclear whether the artificial shrinkage technology is suitable to both early and expanded blastocysts.…”
Section: Resultsmentioning
confidence: 99%
“…There has been considerable professional debate about which blastocyst has better development potential after vitrification. Some people have reported that early blastocysts are more suitable for cryopreservation (Vanderzwalmen et al 2002;Hiraoka et al 2004), whereas others believe that expanded blastocysts have a higher anabiosis rate after cryopreservation (Levens et al 2008). To reduce cryodamage, blastocoeles were collapsed using microneedle or laser drilling prior to vitrification, and this procedure significantly improved the anabiosis rate of blastocysts (Mukaida et al 2006;Cao et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenichiro et al found that no statistically significant differences were observed in the implantation and pregnancy rates between D5 and D6 blastocysts [4]. Some studies, however, indicated that the implantation rate of D5 blastocyst after being frozen and thawed was significantly higher than that in the D6-blastocyst group, whereas the clinical pregnancy rate of the D5 blastocyst was slightly higher than that in the D6 group, but with no statistically significant difference [7]. A recent meta-analysis included 15 articles of frozen-thawed blastocyst transfer, including 2512 freeze-thaw cycles of blastocyst transfer [3].…”
Section: Discussionmentioning
confidence: 99%